Effect of technology awareness and access on the conservation of clean planting materials of vegetatively produced crops: The case of sweetpotato - Okello, A.; Sindi, K.; Shikuku, Kelvin Mashisia; Low, Jan W.; McEwan, M.; Nakazi, F.; Namanda, S.; Babu, A.; Mafuru, J. (Informa UK Limited, 2015)
This study used discrete and count data regression models and data collected from 732 farm households in Tanzania to test the effect of participation on a project designed to break this quality “seed” bottleneck (via technology awareness and targeted access to clean planting materials) on: i) the decision to conserve planting materials during dry periods for future planting and ii) the number of conservation strategies used by farmers.